The perception of employee towards ethical behavior in organization: case study in Duta Village Beach Resort / Zuraida Zakaria - Zakaria, Zuraida (2010)
The purpose of this research is to measure the perceptions of the staff towards the factors that influence an individual ethical behavior in an organization. In today’s competitive business environment, a code of ethics should serve as the foundation upon which employees make decision based on honesty, integrity, confidence and trust. The research is conducted at Duta Village Beach Resort. In completing this research, 30 questionnaires have been distributed to the respondents. The respondents are the staffs in Duta Village Beach Resort included all departments. In order to get the result from this research, the researcher has used SPSS program to analyze data from the information gathered. To analyze the data, the researcher has been used the Reliability Analysis, Frequency Distribution and Descriptive Statistic by using SPSS program. From the findings, the employee had identified what is the most unethical behavior act by an individual. The staffs agree that the person must have their own initiative to develop ethical behavior. However, the staffs also think the ethics policy can be the factor of good organizational ethical practices